How (and why) to ask the older cancer patient about sexual health and sexual minority status. Issue 4 (May 2020) - Cathcart-Rake, Elizabeth; O'Connor, Jennifer M.; Jacobson, Alison; McGuire, Lois; Jatoi, Aminah
Abstract: Sexual health and sexual minority status are often undiscussed during oncology visits. Yet, these topics should be addressed in older cancer patients in order to help mitigate the sexual side effects of cancer treatment and to acknowledge – and, at times, help provide – the social support older patients need during their cancer journey. This paper describes 4 tips on how cancer healthcare providers can broach the topics of sexual health and sexual minority status in an oncology clinic.